The Influence of Stannous Octoat Concentration as Catalyst on Poly Lactic Acid Synthesis from Banana Peel Waste (Musa Paradisiaca Linn) - Pebriyanti, Dita; Azwar, Edwin; Darni, Yuli (Indonesian Journal of Chemical Science, 2021)
One of the biopolymers currently being researched is Poly lactic Acid (PLA). This is due to its high biodegradability so that it is classified as an environmentally friendly polymer. This study aims to obtain the best catalyst concentration and polymerization time of lactic acid in obtaining a high yield of poly lactic acid. PLA made in this study uses lactic acid from the raw material of Kepok banana peel waste. The polymerization of lactic acid into poly lactic acid was carried out using the Ring Opening Polymerization method. Where the stannous octoate catalyst concentrations varied were 5%, 6% and 7% and the reaction time was 80 minutes, 100 minutes and 120 minutes. The analysis used is functional group analysis using Fourier Transform Infra-Red Spectroscopy, melting point test with Difference Scanning Calorymetry and Scanning Electron Microscope test. The results showed that, the values ​​of transition glass and transition melting were obtained, namely 60.5oC and 115.4oC, respectively. The highest amount of poly lactic acid was obtained from the addition of 7% catalyst and polymerization time of 120 minutes, with a yield of 47.442%.